Error Correction Model Analysis in Measuring the Effect of Bank Internal Factors on Mudharabah Deposits for Islamic Commercial Banks - Yudhistira Ardana; Syamsiyah, Nur; Rohmi, Misfi Laili; Renfiana, Lilis (LPPM Universitas Terbuka, 2021)
Islamic bank products to raise public funds can be in the form of demand deposits (wadiah), savings (mudharabah), and deposits (mudharabah). One of the profit-sharing rates in Islamic banks comes from internal factors, namely Return on Assets, Capital Adequacy Ratio, Financing to Deposit Ratio, and Operational Expenses Operating Costs. This study will examine the effect of bank internal factors on mudharabah deposits of Islamic commercial banks using an econometric model, namely the error correction model. Findings. The results showed that the bank's internal variables had a significant effect on mudharabah deposits both in the short and long term. Variables Return on Assets, Capital Adequacy Ratio, and Operational Expenses Operational costs both short and long term have a negative effect on mudharabah deposits.